2018
DOI: 10.1097/md.0000000000010843
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between body mass index changes during chemotherapy and prognosis of patients with advanced colorectal cancer

Abstract: We investigated the relationships between body mass index change (ΔBMI) and prognoses and clinical effects of patients with advanced colorectal cancer (CRC).From January 2008 to December 2012, 224patients with stage IV CRC were diagnosed in our hospital, and their clinical and pathological data were collected for this retrospective study. These patients were divided into lowΔ BMI group (ΔBMI ≤-0.45 kg/m) and high ΔBMI (ΔBMI >-0.45 kg/m) group.After 2 cycles of chemotherapy, there were no significant difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Similarly, the study by Hopirtean et al ( 24 ) indicated that patients with a BMI of less than 27 had a significantly longer median PFS compared to those with a BMI greater than 27. In a 2018 study by Cong et al ( 22 ), no significant difference was found in median PFS between groups with high △ BMI and low △BMI.…”
Section: Resultsmentioning
confidence: 91%
“…Similarly, the study by Hopirtean et al ( 24 ) indicated that patients with a BMI of less than 27 had a significantly longer median PFS compared to those with a BMI greater than 27. In a 2018 study by Cong et al ( 22 ), no significant difference was found in median PFS between groups with high △ BMI and low △BMI.…”
Section: Resultsmentioning
confidence: 91%
“…Geographically, 24 publications were from Europe, 10,33,35,42,243,253,266,268,272,276–279,282,284,291,293,296–298,303,308,310,311 20 from North America, 30–32,34,37,41,238,240,244,249,250,254,265,274,283,285,287,288,301,309 19 from East or Southeast Asia, 36,239,241,246,247,251,252,256,258,262,264,269,280,290,294,295,302,305,307 four from Australia/New Zealand, 242,255,299,300 and 18 from mixed geographic locations 248,257,259,273,275 or elsewhere 245,260,261,263,267,270,271,281,286,289,292,304,306 . Most publications ( n = 54) involved cancer survivors of any stage, 10,30,33,35,36,41,42,238,239,241–245,247,248,250,252,253,256,260,261,263,266–268,270,271,274,277,279,281–284,286,288–290,292–294,296,298,300,302–308,310,311 28 of which also included metastatic cancer survivors (median = 19.6%, range = 6%–58.9%; seven publications did not report % metastatic); 8 included stage II–III, 31,32,37,240,258,259,275,280 9 included stage III or locally advanced…”
Section: Resultsmentioning
confidence: 99%
“…There were 13 studies (12 publications) on weight change and all-cause mortality, 41,242,[248][249][250]254,272,273,275,280,297,301 four studies (four publications) on weight change and colorectal-cancer-specific mortality, 41,242,248,250 10 studies (nine publications) on weight change and cancer recurrence/disease-free survival, 249,254,258,273,275,280,291,297,309 and one study on weight change and cardiovascular mortality. 41 A total of six studies (six publications) were on BMI change and all-cause mortality, 248,262,264,275,278,287 one study on BMI change and colorectal cancer-specific mortality 248 and three studies on BMI change and cancer recurrence/disease-free survival. 254,275,278 There was only one study on waist circumference and recurrence/disease-free survival.…”
Section: Study Selection Processmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Some influential factors include age, gender, performance status, histopathology type, cancer location, and circulating cell tumor levels. [9][10][11] Based on American Cancer Society research, the incidence of early age-onset (EAO) colorectal cancer has increased while the incidence of late age-onset (LAO) colorectal cancer tends to decrease. 12 In colorectal cancer, early age onset is significantly associated with the microsatellite instability pathway and the development of hereditary cancer syndrome, better known as Lynch syndrome.…”
Section: Introductionmentioning
confidence: 99%